Preparação e avaliação de propriedades de materiais híbridos de celulose com polianilina e polióxido de etileno - Maeda, Vinicius Cavalheiro [UNIFESP] (2017)
In recent years, there has been a growing interest in the development of methods which employ biopolymers as support to immobilize other polymeric materials. Among the biopolymers, cellulose is one of the most used due to its abundance, non-toxicity, and because it is obtained from a natural resource. Nevertheless, due its insolubility in common solvents, the biopolymer is not easily processed. Therefore, the search for new methods to overcome this problem is very required. In this Project, it was showed new methods to prepare films of a modified cellulose, called hydroxypropyl methylcellulose (HPMC) and polyaniline (PANI) to be used as conductive papers (GOAL 1) and to obtain films of non-modified cellulose (CEL) and poly(ethylene oxide) (PEO) for lithium-ion batteries (GOAL 2). The films of HPMC and PANI were prepared in homogeneous medium (aqueous medium), where both HPMC and PANI were soluble. It was obtained self-supported and green films. The green color is characteristic of polyaniline on the most conductivity form, the emeraldine form. The films have showed electroativity characteristic of polyaniline and conductivity around 10-3Scm-1 . Therefore, they can be classified as conductive papers. It was also noted that the addition of HPMC in PANI, enhanced the mechanical properties of the films. Films of PEO containing different amounts of non-modified cellulose (CEL) were also prepared by a new method, where cellulose is dissolved in ionic liquid. The addition of cellulose decreased PEO crystallinity, as desired. However, the conductivity of the film of PEO containing 5% of cellulose and lithium salt showed values around 10-5Scm-1, which is not enough to be employed as electrolyte for lithium-ion battery.